Home-Start Parenting Program untuk Meningkatkan Fungsi Emosi Ibu dalam Pengasuhan Anak Usia Dini - Yulia Nur Annisa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
This research driven by the phenomena that majority of mothers have poor understanding on her role as the first educators for their children and the significance of her emotion function in optimizing the child development. The purpose of research was to test the effectiveness of home-start parenting program in improving maternal emotional function. This research used a quasi-experimental design with a single subject. Subjects of research were three mothers who have low levels on their emotional functions. Data were analyzed by analysis of visual inspection to see the trajectory of the line graph and statistical analysis used the overlap data to test the effectiveness of the intervention. The result showed the occurrence of significant difference in scores between baseline phase and the intervention with increasing maternal emotional function scores level. These findings suggested that home-start parenting programs effective in improving the quality of maternal emotional function. Hence the home-start parenting programs can be used as a model of intervention in early childhood parenting.